AB1004 Inter-Rater Reliability of the US-7 Score in A Population of Volunteers: is A Post-Hoc Analysis of Still Images Comparable to the Dynamic Analysis? Results from the "Rheuma-Truck" Cohort. (10th June 2014) - Sewerin, P.; Vordenbäumen, S.; Brinks, R.; Liedmann, A.; Ohrndorf, S.; Backhaus, M.; Sander, O.; Kümmel, M.; Schneider, M.; Ostendorf, B.
Abstract : Objectives: To investigate the value of a follow-up analysis of ultrasonographic still images versus dynamic investigation using the US-7 ultrasound score. Methods: "Rheuma-Truck" was a mobile rheumatology office located in different city center of North Rhine Westphalia offering a screening for rheumatic diseases including Rheuma-Check questionnaire, lab-tests (MCV capillary test), imaging (US, capillaroscopy), and if positive a consultation with a rheumatologist to everybody free of charge. Ultrasound (MyLab 25 Gold, Esaote linear scanner, 15, Typ LA435) of the dominant hand of 605 volunteers was performed. Moreover in 236 of these volunteers the foot was obtained by ultrasound. Thus a total of 3497 joints were examined by ultrasound. Live images were analyzed according to the US-7 scoring system dynamically on site by a trained rater. Still images were stored in a standardized manner in section planes according to US7. These images were assessed by 3 additional experts blinded to the dynamic scoring. The agreement upon all four raters is assessed in two measures a(0) and a(1). These are the percentages of study subjects who are rated equally (a(0)) or equally up to ±1 score point (a(1)) by all four raters. Results: The mean age of the investigated cohort was 52.72 years (min. 10, max. 89 years). Sex distribution shows 72.2% females and 27.8% males. 181 (29.9%) volunteers displayed any inflammatory sign according to US-7 scoring. Using a(0) (all raters rated all subject equal) dorsal wrist showed an accordance between all 4 raters of 62%, the palmar wrist of 98%, the ulnar wrist of 87%, MCP-2 of 77%, MCP-3 85%, PIP-2 70%, PIP-3 81%, MTP -2 72% and MTP-5 96%. Using a(1) (up to ±1) we obtained accordance's of the dorsal wrist of 87%, palmar wrist 100%, ulnar wrist 94%, MCP-2 94%, MCP-3 94%, PIP-2 91%, PIP-3 91%, MTP-2 89% and MTP-5 98%. The accordance between still images and dynamic assessment according to a(1) was 100% for the palmar wrist, 100% for the ulnar wrist, 100% for MCP-2, 100% for MCP-3, 97% for PIP-2, 100% for PIP-3, 100% for MTP -2, and 100% for MTP-5 using the US-7 scoring system. Conclusions: Inter-rater reliability (between all 4 raters) was good with an average of 93.1%. The accordance between still images and dynamic interpretation by using the US-7 scoring system was excellent with 99.6% consensus. Post-hoc evaluation of still images is a valid and reliable tool for the evaluation and interpretation of the US-7 scoring system as shown here in a population of volunteers. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3636